THE ROLE OF THE EDUCATOR IN DEVELOPING THE CHILD’S INTELLECTUAL AND CREATIVE POTENTIAL - Gulbahor Khamidova; Medvedeva Olga Anotolievna (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Annotation: This article examines the multifaceted and crucial role of the educator in fostering the intellectual and creative potential of children. Beyond the traditional function of imparting knowledge, contemporary pedagogy emphasizes the educator’s responsibility to cultivate critical thinking, problem-solving skills, curiosity, and imaginative expression. The article explores how educators act as facilitators, mentors, motivators, and designers of enriching learning environments. It delves into specific pedagogical strategies, such as creating inquiry-based learning opportunities, promoting divergent thinking, encouraging risk-taking, and providing differentiated instruction. Furthermore, the article highlights the importance of the educator’s own intellectual curiosity and creative disposition as a model for children. Ultimately, it argues that a dynamic and supportive educator is indispensable in unlocking and nurturing the full intellectual and creative capabilities of every child.